Alveolar and neotropical echinococcosis - S. B. Chuelov; A. L. Rossina (LLC "Diagnostics and Vaccines", 2022)
The urgency of the problem of human alveolar and neotropic echinococcosis is due to polymorphism and the severity of clinical manifestations. The purpose and result of the work is to summarize the data available in the literature on the etiology, epidemiology, clinic, diagnosis, treatment, prevention of alveolar and neotropic echinococcosis in humans. Conclusion. The causative agent of human alveolar echinococcosis is E. multilocularis, neotropic - E. vogeli, E. oligarthra. The liver and lungs are most often affected, less often other organs of the abdominal cavity, bones, brain, spinal cord, eyes, etc. Diagnostics is carried out on the basis of a complex of clinical, instrumental, serological, molecular genetic studies. Treatment includes surgical removal of parasitic cysts and drug therapy.